AN ANALYSIS OF SLANG WORD USED IN THE LAST RESCUE MOVIE - Sutrisna, I Wayan Ebik Arya; Suastini, Ni Wayan; Aryaningsih, Ni Nyoman Deni (ID Solutions, 2023)
This research was made to find out and examine the meaning of slang, the types of slang and the types of meaning contained in the film that is used as data, the film entitled The Last Rescue, this film tells the journey of a Private James Lewis and his friends surviving attacks and pursuit of the Nazis. This study uses qualitative methods to collect data from the formulation of the problem as much as possible so that it can be researched, describes and explains the problems found. In this data research is carried out by taking from the script, watching the film used as research and applying it to several stories used in the research. This research is similar to the theory of slang words proposed by Kipfer and Chapman (2007) with the title of the book